2012
DOI: 10.1016/j.apenergy.2011.12.101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of the viscosity of nanofluids at low temperatures

Abstract: The effects due to temperature and shearing time on viscosity for Al 2 O 3 /water and CNT/water based nanofluids at low concentration and low temperatures are experimentally investigated. The viscosity data were collected using a stress-controlled rheometer equipped with parallel plate geometry under up and down shear stress ramp. CNT and Al2O3 water based nanofluids exhibited hysteresis behaviour when the stress is gradually loaded and unloaded, depending also on shearing time. Experiments also showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(64 citation statements)
references
References 28 publications
6
47
0
Order By: Relevance
“…As can be seen from Figures 5a and 5b, the nanofluid with a 0.5% weight fraction has the highest pressure drop values compared to the base fluid and the nanofluid with a 0.05% weight fraction for both types of glass. Also, the pressure drop of the nanofluids increases when the Reynolds number increases, as reported by Aladag et al (2012) and Halelfadl et al (2015). With regard to the pressure drop, almost identical results were obtained for the nanofluid at a 0.05% weight fraction and the base fluid, with similar pumping power and heat transfer.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…As can be seen from Figures 5a and 5b, the nanofluid with a 0.5% weight fraction has the highest pressure drop values compared to the base fluid and the nanofluid with a 0.05% weight fraction for both types of glass. Also, the pressure drop of the nanofluids increases when the Reynolds number increases, as reported by Aladag et al (2012) and Halelfadl et al (2015). With regard to the pressure drop, almost identical results were obtained for the nanofluid at a 0.05% weight fraction and the base fluid, with similar pumping power and heat transfer.…”
Section: Resultssupporting
confidence: 64%
“…Phuoc et al (2011) show experimentally that the dynamic viscosity of CNT nanofluids increases with the volume concentration. Many studies have shown that the dynamic viscosity of nanofluids decreases as the temperature increases (Aladag et al, 2012). Other effects may also influence the dynamic viscosity and rheological behavior of CNT-based nanofluids, such as the presence of agglomerates (Chen et al, 2013), thixotropic behavior (Estellé et al, 2013), and the synthesis methods of the CNT.…”
Section: Introductionmentioning
confidence: 99%
“…This result was supported by previous researches in which temperature played an important role in affecting viscosity of nanofluids, where viscosity decreased at a higher temperature [39,40]. At higher temperatures, the particles in nanofluids become active and can cause van der Waals forces and hydrogen bonds to break, thereby decreasing viscosity.…”
Section: Viscositysupporting
confidence: 78%
“…nano-particles, CNT) in a base fluid (nanofluid) has evolved over the past decade. The experiments have unveiled improvements in the rheological (Aladag et al 2012;Chen et al 2011;Jyothirmayee Aravind et al 2011;Lei et al 2008;Murshed et al 2008;Hobbie and Fry 2007;Vakili-nezhaad and Dorany 2009;Phuoc et al 2011;Liu et al 2005) as well as in the thermal (Ding et al 2006;Hwang et al 2006;Kalinina et al 2011;Ö zerinç et al 2010;Venkata Sastry et al 2008;Xie and Chen 2009;Kleinstreuer and Feng 2011;Choi et al 2001;Karthikeyan et al 2008;Xie et al 2002) properties of the nanofluid system, compared to its base fluid.…”
Section: Introductionmentioning
confidence: 99%